New data on the morphology and distribution of the enigmatic Schouteden’s sun snake, Helophis schoutedeni (de Witte, 1922) from the Congo Basin - Nagy, Zoltán T.; Gvoždík, Václav; Meirte, Danny; Collet, Marcel; Pauwels, Olivier S.g. (Zootaxa, 2014)
The Schouteden’s sun snake is the sole representative of its genus, and was originally described by the Belgian herpetologist Gaston-François de Witte as a colubrid, Pelophis schoutedeni (de Witte 1922). Twenty years later, the new generic name Helophis was established by de Witte & Laurent (1942) because the generic name Pelophis was preoccupied by Pelophis Fitzinger, 1843 [type species: Brachyorrhos (now Enhydris) alternans Reuss, 1834]. De Witte (1922) and de Witte & Laurent (1942) gave data on two syntypes (Fig. 1), which are preserved in the herpetological collection of the Royal Museum for Central Africa in Tervuren, Belgium. One, RMCA R.2468, was found in Tondu (at Lac Tumba, Équateur Province, Democratic Republic of the Congo = DRC), while the other, RMCA R.2469, was collected in Kwamouth (“Moyen-Congo”, now Bandundu Province, DRC). Both were collected by Henri Schouteden in 1921. In the original description, no information was given about the sex of the syntypes. De Witte & Laurent (1942) reported a third specimen (RMCA R.11551) from Léopoldville (today Kinshasa), which was collected in 1937 by Henrard. Since then, this snake species was almost forgotten, and the genus has remained monotypic. To our knowledge, no photographs of living specimens of this species have been published so far. In general, very little is known about the distribution, biology, conservation status or even the phylogenetic relationships of this vividly colored snake species. Although several works listed Helophis schoutedeni as being part of the Congo Basin (DRC) snake fauna (e.g. Kusamba 1990; Meirte 1992; Trape & Roux-Estève 1995; Broadley 1998) sometimes including a basic identification key, no new information was given. Moreover, no recent field guides of the Central African region (e.g., Chippaux 2006) include this snake species. Regarding its classification, Broadley (1998) considered it as a natricine species (Natricinae) while in The Reptile Database (Uetz & Hošek 2013) it is listed as Colubridae incertae sedis, similarly like in Pyron et al. (2013), where Helophis was missing from their phylogenetic meta-analysis.